2018
DOI: 10.3389/fmicb.2018.00705
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Monocropped Jerusalem Artichoke Changed Soil Bacterial Community Composition and Ammonia-Oxidizing and Denitrifying Bacteria Abundances

Abstract: Soil microbial communities have profound effects on the growth, nutrition and health of plants in agroecosystems. Understanding soil microbial dynamics in cropping systems can assist in determining how agricultural practices influence soil processes mediated by microorganisms. In this study, soil bacterial communities were monitored in a continuously monocropped Jerusalem artichoke (JA) system, in which JA was successively monocropped for 3 years in a wheat field. Soil bacterial community compositions were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 70 publications
5
28
0
Order By: Relevance
“…This result is consistent with the general findings that the mixture has positive function in soil microbial community compositions (Zeng et al, 2019). As already shown in other studies, effects of mixed cropping or intercropping on microbial abundance, diversity, and community structure are remarkably different from those of monoculture soil (Zhou et al, 2017(Zhou et al, , 2018. Similarly, Latz (2015) reported that the mixture increases microbial community, diversity, and structure in the rhizosphere soil.…”
Section: Effects Of Pf Mixed Turfgrass On Soil Microbial Abundance Dsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with the general findings that the mixture has positive function in soil microbial community compositions (Zeng et al, 2019). As already shown in other studies, effects of mixed cropping or intercropping on microbial abundance, diversity, and community structure are remarkably different from those of monoculture soil (Zhou et al, 2017(Zhou et al, , 2018. Similarly, Latz (2015) reported that the mixture increases microbial community, diversity, and structure in the rhizosphere soil.…”
Section: Effects Of Pf Mixed Turfgrass On Soil Microbial Abundance Dsupporting
confidence: 92%
“…Compared with PP, the PF mixture increased the relative abundance of Proteobacteria and Acidobacteria by 6.36 and 21.90%, respectively, whereas that of Actinobacteria decreased by 38.78% (Figure 3). The difference of relative abundance in Actinobacteria between PF mixture and PP monoculture might be much more related to the different quality of SOM released by turfgrass roots in PP and PF soils, resulting in changes of the groups with the ability to degrading specific organic substrates (i.e., lignocellulose degradation) as reported by several authors (Větrovský et al, 2014;Zhou et al, 2017Zhou et al, , 2018. Moreover, Actinobacteria is positively related with the pH (Zhou et al, 2017); the pH value decreased by 6.67% from the PP to the PF, which might be one of the reasons for decreasing the relative abundance of Actinobacteria.…”
Section: Changes Of Microbial Taxa In Response To Pf Mixed Turfgrassmentioning
confidence: 82%
See 2 more Smart Citations
“…As a major determinant, plants can shift their soil microbial communities through the accumulation of litter and rhizodepositions in the soil under continuous monocropping conditions, thereby altering subsequent plant growth [11,12]. Moreover, other factors such as phytotoxic compounds, soil-borne pathogens, soil physicochemical property changes, and nutrient de ciency can also contribute to the diversity of microbial communities [7,13,14]. Many plants have been reported to suffer from high mortality, declines in yield and quality, and stunting caused by continuous monocropping systems, such as notoginseng [15], soybean [16,17], rice [18], peanut [7], and cucumber [19].…”
Section: Introductionmentioning
confidence: 99%